Web design and its effect on key variables associated with online consumer behavior in the retail sector - García-Salirrosas, Elizabeth Emperatriz (2023)
This study examines the effect of web design on the generation of electronic word of mouth (EWOM) through the satisfaction of e-commerce consumers in the retail sector. To this end, three main objectives were proposed: (1) Evaluate the effect of web design on the perception of security, perceived enjoyment, perceived usefulness and perceived risk of the e-commerce consumer in the retail sector; (2) Evaluate the effect of customer service, perception of security, perceived enjoyment and perceived usefulness on consumer satisfaction in e-commerce in the retail sector; and (3) Explain the positive effect of customer satisfaction and the negative effect of perceived risk on the generation of E-WOM. A study was carried out using a quantitative approach with a nonexperimental and cross-sectional design. Through non-probabilistic convenience sampling, a total of 422 questionnaires from consumers in the retail sector were collected. A partial approach was used to analyze the data. Least Squares PLS-SEM by using SmartPLS. The results show the significant positive effect of web design on the perceptions of security, customer service, and customer satisfaction. And a negative effect on risk perception. Furthermore, this study revealed the mediating effects of risk perception, security perception, and quality of customer service in the retail sector. This study has theoretical, practical, social, and customer management implications, so it will be useful in academic, social, and business areas. The results show the positive and significant effect of web design on the perception of security, enjoyment, and usefulness of online shopping. The negative and significant effect of web design on risk perception was also demonstrated; furthermore, this study revealed the positive and significant effect of perceived usefulness, enjoyment, security, and electronic service on customer satisfaction in online shopping. Finally, the negative and significant effect of risk perception on the generation of electronic word of mouth and the positive and significant effect of satisfaction on the generation of electronic word of mouth were demonstrated.